2021
DOI: 10.1371/journal.pone.0253083
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Transurethral Enucleation of the Prostate: Is it a size-independent endoscopic treatment option for symptomatic benign prostatic hyperplasia?

Abstract: Background Bipolar Transurethral Enucleation of the Prostate (B-TUEP) is recommended as a first-choice treatment for benign prostatic obstruction in prostates >80 ml. Differently, B-TUEP is only considered as an alternative option after TURP for smaller prostates (30–80 ml). The aim of our study is to assess the relation between prostate size and surgical outcomes after B-TUEP. Methods We performed a retrospective analysis of data collected from 172 patients submitted to B-TUEP. Patients were segregated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
9
1
Order By: Relevance
“…Moreover, to the best of our knowledge, only one previous study has compared surgical efficiency, postoperative functional outcomes, and complication rates according to various prostate volume ranges. 7 Furthermore, few studies have evaluated the association between a wide range of prostate volumes and the surgical outcomes of TUEB, especially with long-term follow-up. Therefore, we aimed to evaluate the perioperative efficiency and postoperative functional outcomes according to a wide range of prostate volumes within a 1-year postoperative follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, to the best of our knowledge, only one previous study has compared surgical efficiency, postoperative functional outcomes, and complication rates according to various prostate volume ranges. 7 Furthermore, few studies have evaluated the association between a wide range of prostate volumes and the surgical outcomes of TUEB, especially with long-term follow-up. Therefore, we aimed to evaluate the perioperative efficiency and postoperative functional outcomes according to a wide range of prostate volumes within a 1-year postoperative follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…1 B). Our surgical technique is similar to that reported by Bebi et al.. 7 TUEB was performed as described below ( Fig. 2 ), which was applied to every TUEB case, regardless of the prostate volume or shape of the prostatic lobes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B-TUEP has been recognized to provide symptom relief for BPH patients with prostates of almost any size, with definite efficacy and safety (15). Moreover, some researchers have confirmed that the incidence of body pain/discomfort, decreased physical pleasure, and difficulty in ejaculation of patients after B-TUEP is lower than that of holmium laser enucleation of prostate (HoLEP) (16).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the excellent hemostatic effect of bipolar technologies in treating BPH, Professor Liu, a Chinese scholar, innovatively combined bipolar plasma with his proposed intraluminal prostate enucleation using the mirror sheath as a finger in 2002 to gradually peel off the hyperplastic glands along the prostate surgical envelope under direct visualization and thoroughly treat prostate hyperplasia [4]. Subsequently, multiple randomized controlled studies have shown that bipolar plasma endoscopic enucleation of the prostate was associated with less blood loss, shorter hospital stay and catheter indwelling time, and was not limited by prostate volume [5][6][7]. Additionally, it has become increasingly widely used with the emergence of various energy platforms.…”
Section: Introductionmentioning
confidence: 99%